Cathodic stripping voltammetry of trace Mn(II) at carbon film electrodes - Filipe, Olga M. S. (2003)
A sensitive voltammetric method is presented for the determination of tract levels of Mn (II) using carbon film electrodes fabricated from carbon resistors of 2 [Omega]. Determination of manganese was made by square wave cathodic stripping voltammetry (CSV), with deposition of manganese as manganese dioxide. Chronoamperometric experiments were made to study MnO2 nucleation and growth. As a result, it was found to be necessary to perform electrode conditioning at a more positive potential to initiate MnO2 nucleation. Under optimised conditions the detection limit obtained was 4 nM and the relative standard deviation for eight measurements of 0.22 nM was 5.3%. Interferences from various metal ions on the response CSV of Mn(II) were investigated, namely Cd(II), Ni(II), Cu(II), Cr(VI), Pb(II), Zn(II) and Fe(II). Application to environmental samples was demonstrated.